DUKUNGAN MODAL SOSIAL DAN MODAL BUDAYA PADA KESEHATAN IBU DAN ANAK DI DESA TEMORAN KABUPATEN SAMPANG PROPINSI JAWA TIMUR - Ajeng Kusuma Wardhani (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2016)
Indonesia is still facing serious problems in terms of maternal and child health. From all districts and cities in Indonesia, one of district that has high numbers of maternal and child health is in Sampang East Java. From all sub-districts in this district, there is one sub-district that has a good achievement namely Omben. This research was conducted on Temoran village in Omben subdistrict that has purposes; 1) to explore the concept of culture in traditional societies of Sampang district related to maternal health (pregnancy, childbirth, postpartum, and KB), 2) to explore the involvement of non-medical personnel in health services for mothers and their interaction with medical personnel, and 3) to find out the right capital that must be held by the health workers to support their performance in terms of traditional public health. This study was conducted through qualitative methods using ethnography design. Primary data was collected by in-depth interviews and participant observation. The results showed some cultural elements in the society of Sampang Madura related to the concept of maternal and child health and the close engagement of traditional birth attendant during pregnancy, childbirth, postpartum, and newborn. The unique cultural elements of Madura placing medical personnel, particularly midwives, as an intermediary between the medical and culture practice. In this position, the village midwife is not only required to have medical skills, but also cultural and social capital so that the practice and all of the health programmes can be accepted and implemented by the community. Keywords: maternal and children health, cultural capital, social capital